Tennessee wild hog management - Yoest, Chuck, speaker; Higginbotham, Billy, moderator; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
In 2010 the Tennessee Wildlife Resources Agency (TWRA) acknowledged the failure of harvest-based management to control wild hog (Sus scrofa) populations and the need to shift focus to a more aggressive statewide wild hog eradication program. Recognizing the problem was beyond the scope of the TWRA, organizations were invited to partner in the future of Tennessee's wild hog management. This nascent group focused on proven methods used in states with much smaller hog populations based on three tenets: 1) eliminating incentives to illegally transport and release wild hogs, 2) increasing opportunities for landowners to control wild hogs, 3) and outreach. Following these tenets, wild hog populations have been lowered and some disjunction pockets eliminated across the state. These accomplishments would not be possible by any entity (e.g., TWRA) acting alone. Success is due to the partnership known as the Wild Hog Eradication Action Team (WHEAT) which grew from four partners to a 24 member organization leading wild hog management in Tennessee. WHEAT brings great value to statewide implementation of the three tenets through development of hog management regulations, collaborative outreach, and lobbying. Program success is due to the diversity of partnerships and the ability to guide efforts, remove obstacles, and educate. Recent shifts in Tennessee's wild hog management likely would have failed without the contributions of WHEAT. As a result, we recommend any agencies considering major shifts in wild hog management: 1) do not implement a harvest-based program; 2) adopt the three tenets; and 3) develop an overarching, guiding partnership.
A case history of a politically charged issue - wild pigs in Tennessee
Moderator: Billy Higginbotham.
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses